PERAN STRATEGIS AKTIVIS PEREMPUAN NURUL JANNAH AL FIRDAUS DALAM MEMBENTUK KESADARAN BERAGAMA PEREMPUAN MISKIN KOTA - Hasanah, Hasyim (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2013)
Religious awareness is conscious and recognize the potential, as well as carrying out religious moral values. This is important, because each individual has a duty of chalips that must be directed and developed. Purposes of the study describes the strategic role of women activists Nurul Jannah al-Firdaus in forming religious awareness of poor urban women. This research applying descriptive qualitative with a psychophenomenological approach. The results of research presented the strategicrole of women activists Nurul Jannah in forming religious awareness of poor urban women, that is shown by active involvement through mentoring, education, learning, thus growing independence, and awareness in performing religious rituals on poor urban women